A field guide to Christian nonviolence : key thinkers, activists, and movements for the gospel of peace - Cramer, David C.; Werntz, Myles (Grand Rapids, MI. Baker Academic, 2022)
Christian nonviolence is not a settled position but a vibrant and living tradition. This book offers a concise introduction to diverse approaches to, proponents of, and resources for this tradition. It explores the myriad biblical, theological, and practical dimensions of Christian nonviolence as represented by a variety of twentieth- and twenty-first-century thinkers and movements, including previously underrepresented voices. The authors invite readers to explore this tradition and discover how they might live out the gospel in our modern world.
Preface -- Acknowledgements -- Introduction -- Nonviolence of Christian discipleship: Following Jesus in a world at war -- Nonviolence as Christian virtue: Becoming a peaceable people -- Nonviolence of Christian mysticism: Uniting with the God of peace -- Apocalyptic nonviolence: Exposing the power of death -- Realist nonviolence: Creating just peace in a fallen world -- Nonviolence as political practice: Bringing nonviolence into the public square -- Liberationist nonviolence: Disrupting the spiral of violence -- Christian antiviolence: Resisting sexual and gender-based violence --
Includes bibliographical references (pages 153-173) and index.
Keywords: Nonviolence -- Religious aspects -- Christianity